Proceedings of the Companion Publication of the 2015 Annual Conference on Genetic and Evolutionary Computation 2015
DOI: 10.1145/2739482.2768419
|View full text |Cite
|
Sign up to set email alerts
|

locoGP

Abstract: We present locoGP, a Genetic Programming (GP) system written in Java for evolving Java source code. locoGP was designed to improve the performance of programs as measured in the number of operations executed. Variable test cases are used to maintain functional correctness during evolution. The operation of locoGP is demonstrated on a number of typically constructed "off-the-shelf" hand-written implementations of sort and prefix-code programs. locoGP was able to find improvement opportunities in all test proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 39 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…We also require the programs to be relatively small, so we could run thousands of experiments in reasonable time and avoid the, often very costly, profiling stage of the GI process [6], targeting the whole software instead. With those restrictions in mind, we chose to use the set of 9 sort algorithms and the triangle example provided with the first release of Gin [23] in our study, for which improvements have previously been found using GI [9].…”
Section: Dataset and Toolsmentioning
confidence: 99%
“…We also require the programs to be relatively small, so we could run thousands of experiments in reasonable time and avoid the, often very costly, profiling stage of the GI process [6], targeting the whole software instead. With those restrictions in mind, we chose to use the set of 9 sort algorithms and the triangle example provided with the first release of Gin [23] in our study, for which improvements have previously been found using GI [9].…”
Section: Dataset and Toolsmentioning
confidence: 99%
“…Depending on the particular variant of their framework, line-level or expression-level changes are possible. The locoGP [10] framework developed by Cody-Kenny et al evolves entire Java AST's and acts as an of-the-shelf optimisation tool, while allowing limited customisation via its itness function.…”
Section: Related Workmentioning
confidence: 99%